Advent Care Action: Adventist Community Efforts to Help Flood Victims in South Kalimantan - Janes Sinaga; Juita Sinambela (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
It is hoped that this community service can have a positive impact, especially on communities affected by the South Kalimantan flood disaster. This service is designed to overcome the burden of post-disaster community needs. Advent Cares Action organizes social service events and distributes basic food packages to those in need. The community service approach is carried out through a participatory approach that directly involves members of the South Kalimantan Seventh-day Adventist Church. It is hoped that this social awareness can ease the burden on the needs of communities directly affected by flooding.